2015
DOI: 10.5295/cdg.140474mr
|View full text |Cite
|
Sign up to set email alerts
|

Company financial performance: Does board size matter? Case of the EUROSTOXX50 index

Abstract: This study analyzes the relationship between board size and economic-financial performance in a sample

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 61 publications
2
9
0
Order By: Relevance
“…The results of the study supported the hypothesis (H2) of the study by reporting a negative association with FP as suggested by the AT (Al‐Matari, Kaid Al‐Swidi, Hanim, Fadzil, & Al‐Matari, 2012) that stated that large BS contributes negatively to FP due to communication problem and difficult to make decisions and agreement on the same opinion. The results of the study are similar to the findings of Rahim (2015), Rodríguez‐Fernández (2015), and Yusoff, Mohammed, and Lame (2015).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The results of the study supported the hypothesis (H2) of the study by reporting a negative association with FP as suggested by the AT (Al‐Matari, Kaid Al‐Swidi, Hanim, Fadzil, & Al‐Matari, 2012) that stated that large BS contributes negatively to FP due to communication problem and difficult to make decisions and agreement on the same opinion. The results of the study are similar to the findings of Rahim (2015), Rodríguez‐Fernández (2015), and Yusoff, Mohammed, and Lame (2015).…”
Section: Resultssupporting
confidence: 89%
“…Some of the scholars found a negative relationship between internal CG mechanisms such as NEDs, BS, and CEOD, while some researcher reported a positive impact of internal CG mechanisms on FP around the world. For instance, Alhaji, Wan Yusoff, and Alkali (2012), Rahim (2015), and Rodríguez‐Fernández (2015) reported the negative effect of BS on corporate performance. On the contrary, Gull, Saeed, and Abid (2013) and Javed, Saeed, Lodhi, Uz, and Malik (2013) reported the positive association between BS and FP.…”
Section: Governance Mechanism and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Asset size is significant but negatively affects ROA. Fernandez (2014) in his article supported our result. He found in his study that there existed a strong and negative relation between firm size and financial performance.…”
Section: Panel Data Regression Analysis and Findingssupporting
confidence: 86%
“…This database contains both annual accounts and management details of about 330,000 public and private companies in 41 European countries, including the UK. The reliability of AMADEUS data is evident from its extensive use by other researchers (see, Ahmed, 2015;Rodriguez-Fernandez, 2015). The sample was collected from the AIM because it is one of the few stock exchanges around the world established specifically for SMEs (Mendoza, 2007), and is by far the most successful second-tier market (Colombelli, 2010).…”
Section: Sample Selection and Datamentioning
confidence: 99%